Influence of P sources and rhizobium inoculation on growth and yield of soybean genotypes on Ferric Lixisols of northern Guinea savanna zone of Ghana - Adjei-Nsiah, Samuel; Kumah, J.F.; Owusu-Bennoah, E.; Kanampiu, F.K. (Informa UK Limited, 2019)
Soybean is becoming an important cash crop in northern Ghana. Yet the yields are low due to use of low yielding varieties and limited use of inputs. Greenhouse and field experiments were carried out to evaluate the effects of two phosphorus (P) sources and Rhizobium inoculation on growth, nodulation, P uptake, and yield of three soybean genotypes on Ferric Lixisols of the Guinea savanna zone of Ghana. The P sources were triple superphosphate (TSP) and Morocco phosphate rock (MPR), while the genotypes were TGx 1448-2E, TGx 1904-6F, and TGx 1955-4F. The greenhouse experiment was conducted at the University of Ghana, Legon in a completely randomized design. The field experiment which was carried out in the Upper East region of Ghana was laid out in a split-split plot design with four replicates. In both the greenhouse and field experiments, application of TSP at 30 kg P ha−1 resulted in significantly higher growth and P uptake in shoot compared with MPR and control. Soybean genotypes showed significant differences in growth, nutrient uptake, and grain yield in both the greenhouse and the field experiments. Rhizobium inoculation increased nodule number and dry weight but did not increase grain yield. The genotype TGx 1955-4F appears to show greater potential for increasing productivity of soybean in low P soils in northern Ghana.